Investigative journalism [ - Bradshaw, Paul; Burgh, Hugo de , 1949- (Routledge, 2008)
This introduction to investigative journalism explains how investigative journalism should be understood within the framework of the mass media, how it relates to the legal system, the place of ethics, and the influence of technologies